UN EDIFICIO QUE HABLA: Patología de las edificaciones. - Ríos Soto, Tamy Gabriela (UNIVERSIDAD DE SONORA, 2018)
It’s a common practice to conceal fissures that appear on buildings inhabitated by the human being, in “response” to settlements and movements those buildings and their elements present, but the most correct answers are those that are taken after listening and really listening ( without feigning ) what buildings are telling us. Building Pathology is practiced since buildings talk and this is studied thoroughly by construction experts, and it is even necessary for those buildings to stay under observation, after the adecuate treatment is given to the sick constructions, to identify if it was well understood what they were saying. In the present article, a case in study is cited, where have known how to listen to the “Oftalmology building” of the General Hospital of the city of Hermosillo, Sonora when it was talking, was instrumental to save, not only this construction, but also the lives of those who inhabitated in it and the neighboring buildings.